2017
DOI: 10.1063/1.5009598
|View full text |Cite
|
Sign up to set email alerts
|

Spin-phonon coupling in antiferromagnetic nickel oxide

Abstract: We report the results of ultraviolet Raman spectroscopy of NiO, which allowed us to determine the spin-phonon coupling coefficients in this important antiferromagnetic material. The use of the second-order phonon scattering and ultraviolet laser excitation (k ¼ 325 nm) was essential for overcoming the problem of the optical selection rules and dominance of the two-magnon band in the visible Raman spectrum of NiO. We established that the spins of Ni atoms interact more strongly with the longitudinal than transv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 52 publications
5
73
2
1
Order By: Relevance
“…44,45 Nevertheless, the λ factor has a complex character that depends on the atomic motions involved in the phonon mode, and, for this reason, some compounds seem to be beyond this rule. 24,43,46,47 In case of BCO, the hardening effect observed for (1), (4), (2) and 6 and (c)) modes do not follow this tendency, indicating that each phonon mode has a particular and independent λ factor. However, the correlation between magnetic interactions and the phonon modes in the coupling constant is very complex, and the exact form in which those two properties influence the spin-phonon renormalization effect remains unclear.…”
Section: Resultsmentioning
confidence: 93%
“…44,45 Nevertheless, the λ factor has a complex character that depends on the atomic motions involved in the phonon mode, and, for this reason, some compounds seem to be beyond this rule. 24,43,46,47 In case of BCO, the hardening effect observed for (1), (4), (2) and 6 and (c)) modes do not follow this tendency, indicating that each phonon mode has a particular and independent λ factor. However, the correlation between magnetic interactions and the phonon modes in the coupling constant is very complex, and the exact form in which those two properties influence the spin-phonon renormalization effect remains unclear.…”
Section: Resultsmentioning
confidence: 93%
“…Regarding the magnetic ordering, we investigated second-order magnon scattering using a 405-nm diode laser for excitation since the corresponding two magnon (2M) peak could not be observed for excitation at 325 nm. 41 The 2M peak is in general observable below the Néel temperature as a signature of antiferromagnetic ordering. Based on a detailed investigation of the dispersion for different directions in NiO, Betto et al 42 revealed a reduction of the leading superexchange parameter for films compared to bulk NiO, presumably due to strain.…”
Section: E Raman Quality Metrics Of Nio(100)/mgo(100)mentioning
confidence: 99%
“…The magnetic ordering and lattice dynamics of microcrystalline and singlecrystalline NiO were studied by Raman spectroscopy in [35]- [42]. The Raman spectrum of bulk NiO at room temperature consists of several bands due to secondorder phonon scattering (2TO band at ∼730 cm -1 , TO+LO band at ∼906 cm -1 and 2LO band at ∼1090 cm -1 ) and two-magnon band (at ∼1500 cm -1 ) [35]- [38], [40], [42]. The main difference between green (stoichiometric) and black (defect-reach) bulk NiO was a dramatic increase in the strength of the one-phonon LO mode at 550-560 cm -1 in the black NiO [35].…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between green (stoichiometric) and black (defect-reach) bulk NiO was a dramatic increase in the strength of the one-phonon LO mode at 550-560 cm -1 in the black NiO [35]. The origin of phonon bands was interpreted theoretically using the rigid-ion [43]- [46], shell [47], and first principles [42], [48] models. It was also proposed that some nonmagnetic properties of NiO as zonecentre optical phonon frequencies and Born effective charge tensor are substantially noncubic below the Néel temperature, even assuming the ideal rock-salt structure of the oxide [49].…”
Section: Introductionmentioning
confidence: 99%